2022
DOI: 10.1155/2022/5141773
|View full text |Cite
|
Sign up to set email alerts
|

Medical Cannabis for Gilles de la Tourette Syndrome: An Open-Label Prospective Study

Abstract: Objectives. Assessing the effectiveness and tolerability of medical cannabis (MC) treatment on Gilles de la Tourette syndrome (GTS) patients. Methods. We report on an open-label, prospective study on the effect of MC on adult GTS patients. MC mode of use was decided by the treating neurologist and the patient. Δ9-Tetrahydrocannabinol (Δ9-THC) and cannabidiol (CBD) content within MC product and monthly dose were titrated during the study. Following treatment initiation, patients were assessed after 4 and 12 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 57 publications
0
7
0
7
Order By: Relevance
“…In 2003, the same authors [ 17 ] published a randomized controlled trial involving 24 patients favoring daily THC treatment compared to placebo with significant reduction in tics ( Table ). While these trials have shown promising results, the effect sizes were not as large and consistent as those reported by patients with regards to inhaled cannabis (smoked or vaporized) [ 20 ]. In 2022, Anis et al [ 20 ] published an open-label clinical trial demonstrating good efficacy and tolerability of medical cannabis in adult Gilles de la Tourette syndrome patients ( Table ).…”
Section: Developmentmentioning
confidence: 77%
See 1 more Smart Citation
“…In 2003, the same authors [ 17 ] published a randomized controlled trial involving 24 patients favoring daily THC treatment compared to placebo with significant reduction in tics ( Table ). While these trials have shown promising results, the effect sizes were not as large and consistent as those reported by patients with regards to inhaled cannabis (smoked or vaporized) [ 20 ]. In 2022, Anis et al [ 20 ] published an open-label clinical trial demonstrating good efficacy and tolerability of medical cannabis in adult Gilles de la Tourette syndrome patients ( Table ).…”
Section: Developmentmentioning
confidence: 77%
“…Furthermore, they may cause severe side effects, such as parkinsonism, metabolic syndrome, and hyperprolactinemia, compromising the compliance. Two small, controlled trials have investigated the effect of oral THC in adult Gilles de la Tourette syndrome patients [ 17 , 19 , 20 ]. In 2002, Mueller-Vahl et al [ 19 ] published a double-blind, placebo-controlled, crossover trial of 12 patients (18-66 years) suggesting that a single-dose treatment with THC was effective and safe in the therapy of tics and obsessive-compulsive behavior in Gilles de la Tourette syndrome ( Table ).…”
Section: Developmentmentioning
confidence: 99%
“…A Síndrome de Tourette (ST) é um transtorno de primeira infância, considerado um distúrbio do neurodesenvolvimento, prevalente em cerca de 0,3 -0,8% das crianças em idade escolar, marcada pela presença de múltiplos tiques motores e de pelo menos um tique vocal, sendo eles súbitos, rápidos, recorrentes, irregulares, não rítmicos e por vezes acompanhados de comorbidades psiquiátricas, com duração temporal de pelo menos um ano (Anis et al, 2022).…”
Section: Introductionunclassified
“…Estudos recentes sugerem como um dos possíveis fatores desencadeantes da ST, disfunções nas vias córtico estriatotálamo-corticais, em específico, na via dopaminérgica (ANIS et al, 2022). Além disso, tem-se como outra causa possível, o aumento da ligação do receptor D2 da dopamina no núcleo caudado, que é uma estrutura de substância cinzenta do telencéfalo, localizada ao lado da parede dos ventrículos laterais (Hsu et al, 2021).…”
Section: Introductionunclassified
See 1 more Smart Citation